A Study of DevOps Implementation to Accelerate Software Development in Start-Up Industry - Angeline; Eryc; Indasari Deu (P3M Politeknik Negeri Bengkalis, 2025)
This study explores how implementing DevOps influences perceived productivity in software development within startup companies in Batam, Indonesia. A quantitative method was used through a structured survey involving 261 respondents from ten software houses. Data were analyzed using Structural Equation Modeling (SEM) with AMOS to assess relationships among seven constructs adapted from the Unified Theory of Acceptance and Use of Technology (UTAUT). Results show that Social Influence and Perceived Feasibility significantly affect the Intention to Adopt DevOps, which in turn has a positive impact on Perceived Productivity. Conversely, Performance Expectancy, Facilitating Conditions, and Perceived DevOps Practices show no significant effect. These findings highlight the importance of social support, collaborative culture, and technical readiness in shaping adoption intentions in resource-limited startups. The model demonstrates good fit (CFI = 0.924, TLI = 0.914, RMSEA = 0.065), explaining 74.2% of variance in perceived productivity, with the strongest path between Intention to Adopt DevOps and Perceived Productivity (β = 1.032, p = 0.001).